A Simple Action Plan for Utilities to Secure Their Process Control Systems. Issue 2 (1st February 2014) - Spence, Shannon; Roberson, J. Alan; Morley, Kevin M.
Abstract : Water systems confront a variety of threats on a daily basis, ranging from vandalism to insider jobs to hurricanes and tornadoes. The actual threat is not the point; it's the end game that is most critical. Cybersecurity is an increasingly important issue for water systems. A critical factor is the relative ease with which such attacks can be executed. The perpetrator can remain totally anonymous without risk of exposure as would occur in attempting a physical attack. Cyber‐terrorists are often hundreds or thousands of miles away and take advantage of the Internet to gain access to process controls. As long as water systems rely on process control systems and other automated systems to support their operations, vigilance on the cyber‐front will need to continue.